The 2012 International Joint Conference on Neural Networks (IJCNN) 2012
DOI: 10.1109/ijcnn.2012.6252476
|View full text |Cite
|
Sign up to set email alerts
|

Comparing NARX and NARMAX models using ANN and SVM for cash demand forecasting for ATM

Abstract: a comparative study between NARMAX and NARX models developed with ANN and SVM when used to forecast cash demand for ATMs is conducted. A simple methodology for developing SVM-NARMAX models is proposed. The best results were obtained with NARX-ANN models. In addition no significant differences were found between NARX and NARMAX for both ANN and SVM. Hence it seems advisable to choose simpler models, such as NARX and a user-friendly tool like ANN at least for this particular application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…Non-linear Auto Regressive with Exogenous (NARX) input is a time series non-linear model derived from the Autoregressive exogenous (ARX) linear model and have been widely used for modelling and prediction purposes [19][20][21][22][23][24][25]. The model consists of structure which is repeated in the dynamic network with feedback connections.…”
Section: Narx-ann Modelmentioning
confidence: 99%
“…Non-linear Auto Regressive with Exogenous (NARX) input is a time series non-linear model derived from the Autoregressive exogenous (ARX) linear model and have been widely used for modelling and prediction purposes [19][20][21][22][23][24][25]. The model consists of structure which is repeated in the dynamic network with feedback connections.…”
Section: Narx-ann Modelmentioning
confidence: 99%
“…The combined method showed a better performance than ARX and NARX separately due to ability of combined model structure to model nonlinear dynamical systems [11]. Although NARX models have proved to be a powerful approach to identification of nonlinear phenomena [10][11][12][13], as far as the authors know, no gait events detection with NARX have been reported.…”
Section: Nonlinear Autoregressive Models With Exogenousmentioning
confidence: 99%
“…A number of recent studies, e.g. Acuna et al (2012), Dandekar and Ranade (2015), Mishra and Dehuri (2014), Venkatesh et al (2014), utilise ANN models as a cash forecasting tool. These studies support the superiority of ANN models as forecasting tools.…”
Section: Introductionmentioning
confidence: 99%